2022
DOI: 10.3390/ijms23179722
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic 3D Printing of w/o Pickering Emulsions Containing Bifunctional Drugs for Producing Hierarchically Porous Bone Tissue Engineering Scaffolds with Antibacterial Capability

Abstract: How to fabricate bone tissue engineering scaffolds with excellent antibacterial and bone regeneration ability has attracted increasing attention. Herein, we produced a hierarchical porous β-tricalcium phosphate (β-TCP)/poly(lactic-co-glycolic acid)-polycaprolactone composite bone tissue engineering scaffold containing tetracycline hydrochloride (TCH) through a micro-extrusion-based cryogenic 3D printing of Pickering emulsion inks, in which the hydrophobic silica (h-SiO2) nanoparticles were used as emulsifiers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Specifically, in PCL-TCH scaffolds, ALP was upregulated on day 21, suggesting that PCL-TCH scaffolds promoted osteogenic differentiation, probably when a greater amount of the drug has been released from the scaffold, as shown from the in vitro dissolution study. Similar results have been reported in another study with 3D-printed composite scaffolds (β-TCP/PLGA-PCL) containing tetracycline hydrochloride after 14 days of culture [32]. Similar results were presented in a study by Dayaghi et al, in which magnesium-zinc scaffolds that had been immersed in solutions of different tetracycline concentrations (10-100% w/v), showed that ALP levels were increased in all scaffolds' concentrations with increasing incubation time [53].…”
Section: Bioactive Scaffolds and Their Potential To Bone Regenerationsupporting
confidence: 89%
See 1 more Smart Citation
“…Specifically, in PCL-TCH scaffolds, ALP was upregulated on day 21, suggesting that PCL-TCH scaffolds promoted osteogenic differentiation, probably when a greater amount of the drug has been released from the scaffold, as shown from the in vitro dissolution study. Similar results have been reported in another study with 3D-printed composite scaffolds (β-TCP/PLGA-PCL) containing tetracycline hydrochloride after 14 days of culture [32]. Similar results were presented in a study by Dayaghi et al, in which magnesium-zinc scaffolds that had been immersed in solutions of different tetracycline concentrations (10-100% w/v), showed that ALP levels were increased in all scaffolds' concentrations with increasing incubation time [53].…”
Section: Bioactive Scaffolds and Their Potential To Bone Regenerationsupporting
confidence: 89%
“…With respect to the in vitro dissolution study, our findings demonstrated that TCH is released from the 3D scaffolds at a faster initial pace, followed by a more sustained release rate during the 2-72 h window. This observation is possibly associated with the hydrophilic nature of the drug in combination with the surface-bound drug molecules that get released easier [16,31,32]. Initial burst drug release is a phenomenon that is witnessed in various drug delivery platforms, and it can be controlled by modulating specific parameters, such as the surface of the drug-loaded matrix, its geometry and structure, as well as the type of materials used [33].…”
Section: Bioactive Scaffolds and Their Physiochemical Characteristicsmentioning
confidence: 99%
“…Bone scaffolds contact directly with the cells and provide the extracellular matrix (ECM) for cell adhesion, proliferation, and differentiation. 49–51 rGO has been reported to increase the stability of adsorbed proteins, such as bone morphogenetic protein 2 (BMP-2), and eventually improve cell adhesion, proliferation, and osteogenic differentiation. 52 The osteoblast phenotype is specifically obtained in two stages.…”
Section: Resultsmentioning
confidence: 99%
“…Cryogenic temperatures can significantly minimize enzymatic activity due to the slowed molecular motion and decreased metabolic rates at low temperatures. Enzymes related to scaffold degradation, such as proteases and lipases, may exhibit reduced activity, which produces to slower degradation rates , Ye et al (2022). Similarly, cryogenic temperatures can also affect the cellular metabolism and activity.…”
Section: Introductionmentioning
confidence: 99%